First Trimester Diagnosis of Cantrell Pentalogy: A Case Report - Emel Ebru Özçimen; Ali Sami Gürbüz; Necati Özçimen (Medical Network, 2016)
Pentalogy of Cantrell is a rare syndrome with a deficiency of anterior diaphragm, a midline supraumbilical abdominal wall defect, a defect in the diaphragmatic pericardium, various congenital intracardiac abnormalities and a defect of the lower sternum. Herein a fetus with Cantrell Pentalogy who was diagnosed in the first trimester was presented and discussed in the light of the literature.